2018
DOI: 10.1017/wsc.2018.30
|View full text |Cite
|
Sign up to set email alerts
|

Annual Bluegrass (Poa annua) Biotypes Exhibit Differential Levels of Susceptibility and Biochemical Responses to Protoporphyrinogen Oxidase Inhibitors

Abstract: An annual bluegrass (Poa annuaL.) biotype with limited susceptibility to POST flumioxazin applications was identified in Georgia. The objectives of this research were to quantify tolerance levels of this biotype (R-biotype) to protoporphyrinogen oxidase (PPO) inhibitors and characterize physiological responses to flumioxazin. In dose–response experiments on 3- to 5-tiller plants, flumioxazin and sulfentrazone rates required to reduce dry-shoot biomass 50% from the nontreated were >14.5 and 10.4 times greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Although resistance to PPO-inhibiting herbicides is not widespread in turfgrass systems, species that have evolved resistance are similar to those previously discussed for other modes of action. For example, Yu et al (2018) identified a population of annual bluegrass on a golf course in Georgia that was resistant to POST applications of the PPO-inhibiting herbicide flumioxazin applied at a three-to five-tiller growth stage; however, this biotype was effectively controlled when flumioxazin was applied PRE. The mechanism of resistance in this PPO-resistant annual bluegrass biotype was associated with reduced lipid peroxidation and electrolyte leakage compared to herbicide-susceptible annual bluegrass.…”
Section: Glyphosate-resistant Weeds In Turfgrass (Wssa Group 9)mentioning
confidence: 99%
“…Although resistance to PPO-inhibiting herbicides is not widespread in turfgrass systems, species that have evolved resistance are similar to those previously discussed for other modes of action. For example, Yu et al (2018) identified a population of annual bluegrass on a golf course in Georgia that was resistant to POST applications of the PPO-inhibiting herbicide flumioxazin applied at a three-to five-tiller growth stage; however, this biotype was effectively controlled when flumioxazin was applied PRE. The mechanism of resistance in this PPO-resistant annual bluegrass biotype was associated with reduced lipid peroxidation and electrolyte leakage compared to herbicide-susceptible annual bluegrass.…”
Section: Glyphosate-resistant Weeds In Turfgrass (Wssa Group 9)mentioning
confidence: 99%
“…Different weed species exhibit varying susceptibility to a particular herbicide category ( McElroy and Martins, 2013 ; Yu et al., 2018 ). For example, acetolactate synthase (ALS)-inhibiting herbicides generally provide a narrow weed control spectrum ( Yu and Boyd, 2018 ); ACCase-inhibiting herbicides are only effective for controlling grassy weeds ( McElroy and Martins, 2013 ); nonselective herbicides, such as glyphosate and glufosinate, could nonselectively control all weeds ( Johnson, 1977 ); and synthetic auxin herbicides, such as 2,4-D, dicamba, and MCPA, are only effective for controlling broadleaf weeds ( McElroy and Martins, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Controlling winter weeds in dormant turfgrass can improve the aesthetic value and stand quality of turfgrass. A variety of herbicides including acetolactate synthase (ALS) inhibitors such as trifloxysulfuron, protoporphyrinogen oxidase inhibitors such as flumioxazin, the photosystem II (PS II) inhibitor simazine, synthetic auxins such as dicamba and 2,4-D, photosystem I electron diverter diquat, glutamine synthetase inhibitor glufosinate, and the enolpyruvulshikimate 5-phosphate synthase (EPSPS) inhibitor glyphosate are used for postemergence (POST) control of winter weeds in dormant turfgrass (Brosnan et al 2020a(Brosnan et al , 2020bFlessner et al 2013;Heap 2021;McCullough et al 2016McCullough et al , 2017Yu et al 2015Yu et al , 2018.…”
Section: Introductionmentioning
confidence: 99%